(untitled) (Revista Sapiência: sociedade, saberes e práticas educacionais (2238-3565), 2017)
We discuss in this study the phenomenon of the new religions as a consequence of the cultural dynamics of late modernity. From the Religions Studies, we suggest that “the religious disembedding” over the last centuries permitted the individual religious imagination to gain access to a planetary religious plethora. With greater freedom from institutional constrains, the individual religious imagination went through itineraries to reach self-fulfillment and a new spiritual conscience.